LANGKAH – LANGKAH PEMBENTUKAN BAHAN AJAR DALAM MEREKONSTRUKSI MATERI PERKULIAHAN - Sulistiawati, Sulistiawati (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2020)
Abstract— One way to keep updated material up to date is to reconstruct lecture material. The educational reconstruction described in this paper contains the development of teaching materials using the MER (Educational Reconstruction Model) model developed by Duit et al (2012). Develop models that emphasize students' understanding of what supports. Occurs between the structure of science content and students' initial understanding. In order to explain the structure of content easily understood by students, it must be carried out elementalization (elemantrization) in the form of simplifying the structure of the science content. The act of simplification (elementization) is important because there are still many teaching materials that are not in accordance with the level of understanding of students so that it is not easy to be facilitated by them. Good teaching materials will help students in understanding the material received. To get good teaching materials, there are several characteristics of good teaching materials proposed by Winkel (2004: 331), namely instructional independence, independent, independent, adaptive, and user friendly. Keywords— Reconstruction of lecture material Teaching material Constituent structure Content structure  Abstrak— Salah satu cara agar materi yang diajarkan tetap up to date adalah dengan cara merekonstruksi materi perkuliahan. Rekonstruksi pendidikan yang diuraikan dalam tulisan ini berupa pengembangkan bahan ajar menggunakan model MER (Model of Education Reconstruction) yang dikembangkan oleh Duit et al (2012). Pengembangan model ini menekankan pada aspek pemahaman siswa terhadap apa yang diajarkan. Terjadi kesenjangan antara struktur konten sains dan pemahaman awal peserta didik. Agar penjelasan struktur konten sains mudah difahami oleh peserta didik, maka harus dilakukan elementrisasi (elemantrization) dalam bentuk penyederhanaan struktur konten sains tersebut. Tindakan penyederhanaan (elementrisasi) penting dilakukan karena masih banyak bahan ajar belum sesuai dengan tingkat pemahaman peserta didik sehingga tidak mudah untuk dipahami oleh mereka. Bahan ajar yang baik akan membantu peserta didik dalam memahami materi yang diajarkan. Untuk mendapatkan bahan ajar yang baik ada beberapa karakteristik bahan ajar yang baik yang dikemukakan oleh Winkel (2004: 331) yaitu self instructional, self contained, stand alone, adaptive, dan user friendly. Kata Kunci— Rekonstruksi materi perkuliahan            Bahan ajar          Stuktur konsten      Struktur konten